APAKAH KINERJA KEBERLANJUTAN BERPERAN PADA MANAJEMEN LABA DI LIMA NEGARA ASEAN? - Yolanda, Nike; Widiastuty, Erna (Jurnal Aplikasi Akuntansi, 2024)
This study aims to examine the role of sustainability performance on accrual earnings management in public companies in Southeast Asia. The research sample was on public companies in five ASEAN countries (Indonesia, Malaysia, Singapore, Thailand and Philippines) from 2017 to 2022. Sampling was carried out using a purposive sampling method, obtaining 1,218 company-year observations. The independent variable sustainability performance is measured using ESG scores while the dependent variable earnings management is measured using accrual earnings management. The results of this research provide empirical evidence that sustainability performance has no impact on accrual earnings management. Its means that companies with good sustainability performance tend not to carry out earnings management, whereas if earnings management occurs it is influenced by other factors outside of sustainability performance. This research has implications for investors in making investment decisions regarding companies that report ESG performance and the government regarding the quality of sustainability performance reporting.